Investment, dynamic consistency and the sectoral regulator's obective - Duarte Brito; Pedro Pereira; Jo\~ao Vareda (International Telecommunications Society (ITS), 2011)
We explore the separation of powers between the legislative and the executive branch of government as a way of overcoming the dynamic consistency problem of regulatory policy towards investment. We model the industry as a regulated duopoly. The incumbent is a vertically integrated firm that owns a wholesaler and a retailer. The entrant owns a retailer. Either retailer needs access to the input produced by the wholesaler to operate. The incumbent can make an investment that improves the quality of the input produced by the wholesaler. The regulator sets the access price and is unable to commit. The legislator sets the regulator's objective function and is able to commit. We derive general conditions under which having the legislator distort the regulator's objective function away from social welfare allows increasing the range of parameter values for which it is possible to induce socially desirable investment.
Keywords: L43; L51; L96; L98; 330; Investment; Dynamic Consistency; Regulator's Objective